Hospitality and Tourism Human Resources - HO127 - 202102 - Bailly Velasco, Luis Alberto (2021)
Description The Hospitality and Human Resources course is a theoretical-practical course aims to give the student an overview of the different processes of Human Resources and how they are linked to performance, motivation and achieving company's goals. Purpose In this course students will learn the functions and responsibilities of the human resource department. Students will also learn the different contemporary concepts and methodologies to develop talent management and that provide support to the different operation areas of a hotel. The course contributes directly to the development of general competences of Citizenship (level 2) and specific competence of People Management (level 2). The Pre-requisite is AD170 Organizational Design and Processes.